Isolation and partial characterization of alginate extracted from Sargassum polycystum collected from three habitats in Banten, Indonesia - NIKEN DHARMAYANTI; JATNA SUPRIATNA; ABINAWANTO ABINAWANTO; YASMAN YASMAN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Dharmayanti N, Supriatna J, Abinawanto, Yasman. 2019. Isolation and partial characterization of Alginate from Sargassum polycystum of Banten, Indonesia. Biodiversitas 20: 1776-1785. The utilization of Sargassum polycystum as an alternative alginate source may reduce the dependence on alginate import as currently alginate demands in Indonesia are 100% supplied from overseas. The purpose of this study was to characterize alginate extracted from Sargassum polycystum obtained from three locations with different ecological characteristics. Isolation of alginate was conducted through partial hydrolysis to separate guluronic acid and mannuronic acid followed by freeze-drying and then the parameters were measured qualitatively and quantitatively using FTIR. The results showed that alginate extracted from Sargassum polycystum collected from Lima Island, Ujung Kulon and Binuangeun were 11.48%, 18.62%, and 5.75%, respectively with the viscosity were 35 cP, 62.50 cP, and 81.33 cP, respectively. The test result of partial hydrolysis of alginate showed that guluronic block (GG) in the alginate polymer of Lima Island, Ujung Kulon and Binuangeun were 67.60%, 59.00%, and 41.40%, respectively. These relate to the nature of the gel formed. The alginate from Lima Island tends to be more rigid and less flexible than that from Ujung Kulon and Binuangeun. The findings of this study suggest that there are differences in the concentration of the components of mannuronate and guluronate of Sargassum polycystum across different locations in Banten, Indonesia.